Temporal changes in the epidemiology of sepsis‐related intensive care admissions from the emergency department in Australia and New Zealand. (3rd July 2022) - Jones, Daryl; Moran, John; Udy, Andrew; Pilcher, David; Delaney, Anthony; Peake, Sandra L; ,
Abstract: Objectives: The Australasian Resuscitation in Sepsis Evaluation (ARISE) study researched septic shock treatment within EDs. This study aims to evaluate whether: (i) conduct of the ARISE study was associated with changes in epidemiology and care for adults (≥18 years) admitted from EDs to ICUs with sepsis in Australia and New Zealand; and (ii) such changes differed among 45 ARISE trial hospitals compared with 120 non‐trial hospitals. Methods: Retrospective study using interrupted time series analysis in three time periods; 'Pre‐ARISE' (January 1997 to December 2007), 'During ARISE' (January 2008 to May 2014) and 'Post‐ARISE' (June 2014 to December 2017) using data from the Australian and New Zealand Intensive Care Society Adult Patient Database. Results: Over 21 years there were 54 121 ICU admissions from the ED with sepsis; which increased from 8.1% to 16.4%; 54.6% male, median (interquartile range) age 66 (53–76) years. In the pre‐ARISE period, pre‐ICU ED length of stay (LOS) decreased in trial hospitals but increased in non‐trial hospitals ( P  = 0.174). During the ARISE study, pre‐ICU ED LOS declined more in trial hospitals ( P  = 0.039) as did the frequency of mechanical ventilation in the first 24 h ( P  = 0.003). However, ICU and hospital LOS, in‐hospital mortality and risk of death declined similarly in both trial and non‐trial hospitals. Conclusions: Sepsis‐related admissions increased from 8.1% to 16.4%. During the ARISE study, there was more rapid ICU admission and decreased early ventilation. However, these changes were not sustained nor associated with decreased risk of death or duration of hospitalisation.